Changes in the volatile profiles, organic acid contents, and sugar compositions of durian pulps during long-term frozen storage - Xue, Yi Tan; Misran, Azizah; Jeffery Daim, Leona Daniela; Ding, Phebe; Pak-Dek, Mohd Sabri (Wiley, 2021)
Frozen storage was introduced to maintain the quality and prolong the shelf life of durian pulps. The aim of the present work was to evaluate the changes of organic acids, sugars, and volatile organic compounds (VOCs) in “Musang King” (“MK”) and “D24” pulps under long-term frozen storage. Organic acids in “MK” and “D24” only showed slight decrements, but sugar contents especially sucrose drastically decreased during 1 year frozen storage. Fructose and glucose in both durian pulps increased during the first half period of storage; this might be due to the conversion of sucrose to monosaccharides during storage. Freezing also caused the loss of some VOCs especially sulfur- and ester-containing VOCs in “MK” and “D24” pulps. These results indicated that the flavor losses in “MK” and “D24” were mostly related to the losses of ester-containing compounds rather than organic acids and sugar compositions following 1 year frozen storage.